2022
DOI: 10.1111/mam.12301
|View full text |Cite
|
Sign up to set email alerts
|

The wild boar Sus scrofa in northern Eurasia: a review of range expansion history, current distribution, factors affecting the northern distributional limit, and management strategies

Abstract: The wild boar Sus scrofa is one of the most widely distributed large mammal species in the world, existing on all continents except Antarctica. In the late 20th Century, its geographical range expanded naturally and through intentional releases. Despite the environmental, social, and economic importance of the wild boar, its current distribution in northern Eurasia remains uncertain, and the factors that limit and promote expansion in northern ecosystems are unknown. We aimed to summarise the history of wild b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…Our comprehensive analysis revealed that 1.54% of genes (313 out of 20,306, Ensembl v105) were consistently identified across at least three distinct methods as being under selection, indicating a conservative estimation in this study. Additionally, 0.45% of genes (92 out of 20,306) were corroborated by all four analytical methods (Supplementary Table 7).…”
Section: The Genes Under Selective Sweep and Their Functional Enrichm...mentioning
confidence: 83%
See 3 more Smart Citations
“…Our comprehensive analysis revealed that 1.54% of genes (313 out of 20,306, Ensembl v105) were consistently identified across at least three distinct methods as being under selection, indicating a conservative estimation in this study. Additionally, 0.45% of genes (92 out of 20,306) were corroborated by all four analytical methods (Supplementary Table 7).…”
Section: The Genes Under Selective Sweep and Their Functional Enrichm...mentioning
confidence: 83%
“…The severe low temperatures serve as a strong selective force, especially for species like the wild boar, necessitating adaptations for effective thermoregulation in these frigid zones. Beyond the cold, another major environmental challenge is the scarcity of food resources during the lengthy winter season (20). Thus, uncovering molecular adaptations enabling peripheral or derived populations of wild boar to survive and flourish in the cold Siberian climate and its neighboring regions is a subject of great scientific interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because species responses to environmental factors are scale‐dependent processes, factors related to wild boar habitat suitability and damage risk may manifest at different spatial scales (Falconi et al 2015, Rather et al 2020, Wang et al 2020). Climate is a major determinant of the suitability of wild boar's native habitats and their expansion into other areas (Markov et al 2019, 2022). For example, our results indicate the mean temperature of the coldest quarter and isothermality are most relevant for wild boar habitat suitability at 3.5‐km and 1‐km scales, respectively.…”
Section: Discussionmentioning
confidence: 99%